Description Of Stunting In Children Under Two Years With The Complementary Feeding Sumbang District, Banyumas Regency, Central Java - Ivan Pratama; Titus Priyo Harjatmo (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
One of the nutritional problems in the world is stunting. Stunting is a condition where a toddler has less length or height when compared to age. Stunting is a chronic nutritional problem caused by many factors. One of the factors that can cause stunting is complementary feeding. Infants who are not getting good complementary feeding have a greater chance of growth growth by 6.5 times compared to babies who get enough complementary feeding. The purpose of this study was to determine the description of stunting in the under two years old by giving complementary feeding in the working area of ​​Puskesmas 1, Sumbang District, Banyumas Regency, Central Java. This descriptive analytic study was taken from secondary data using a cross sectional design conducted on 444 mothers who have children aged 6-23 months in the working area of ​​the District 1 Sumbang Puskesmas. The results showed that there was no significant relationship between nutritional status of under two years on the practice of giving complementary feeding (p = 0.06), type of complementary feeding (p = 0.857), and frequency of complementary feeding (p = 0.393). However, there were differences in nutritional status based on age at the first time giving complementary feeding to under two years whose diet was incomplete (p = 0.001) and differences in nutritional status based on the type of complementary feeding given to under two years who washed their hands did not use soap (p = 0.03